A Conversation with Jean‐Louis Bodin. (14th October 2014) - Saporta, Gilbert
Summary Jean‐Louis Bodin has had a distinguished career as an official statistician in the French and European statistical systems, where he has been working for 40 years. Born in 1941 in Bordeaux, the capital city of one of the most famous vineyards in the world, he became graduate of two French prestigious schools, the Ecole Polytechnique in 1963, then the ENSAE (Ecole Nationale de la Statistique et de l'Administration Economique) in 1966. After having spent 20 years in different positions in the French Statistical System, he dedicated the last 20 years of his career to international relations in official statistics and cooperation for strengthening statistical capacities of transition and developing countries. In particular, he was one of the main drafters of the UN Resolution on Fundamental Principles for Official Statistics and of the African Statistical Charter. He is also known for having created AFRISTAT, the Economic and Statistical Observatory of Sub‐Saharan African countries. He was also during years one of the French representatives in the UN Statistical Commission, the UN Conference of European Statisticians and the Statistical Committee Programme of the European Union. Jean‐Louis Bodin has played for 40 years a very active role in national and international statistical societies. He served on many disparate positions in the ISI family: executive director of the International Association of Survey Statisticians from 1981 to 1985 under the successive chairmanships of Gérard Théodore and Leslie Kish, founding member in 1985 with Vera Nyitrai of the International Association for Official Statistics and president of the Association from 1989 to 1991, secretary‐general of the National Organizing Committee of the 47th ISI Session held in Paris in August 1989, Chair of the Programme Coordinating Committee of the 50th ISI Session held in Beijing in August 1995, ISI president‐elect then president from 1997 to 2001, president of the Jury of the Mahalanobis Prize from 2002 to 2005. He was also president of the Société de Statistique de Paris in 1994. He received the certificate of Fellow of the American Statistical Association in 1996 and was a member of the ASA Committee for International Relations in Statistics from 1993 to 1997. He was bestowed in 2006 as a Chevalier de la Légion d'Honneur (Knight of the Legion of Honour) in France and in 1997 as a Kawaleski Orderu Zasługi(Knight of the Order of Merit) in Poland. He received the Medal of Statistical Merit in Vietnam in 2003 and the African Statistical Award bestowed by the UN Economic Conference for Africa in 2012. This conversation was held in June 2013 with Gilbert Saporta in Paris. Gilbert Saporta: Welcome to this interview, Jean‐Louis. I'm delighted that you could spend some time with me to discuss your career, your achievements and your views on some aspects of official statistics. It appears that your professional career as a French official statistician and your participation in ISI activities were tightly linked. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>